Automation, Skills and the Future of Work : What do Workers Think? - Mulas-Granados, Carlos; Boranova, Vizhdan; deChalendar, Alice; Varghese, Richard (Washington, D.C. : International Monetary Fund, 2019)
We exploit a survey data set that contains information on how 11,000 workers across advanced and emerging market economies perceive the main forces shaping the future of work. In general, workers feel more positive than negative about automation, especially in emerging markets. We find that negative perceptions about automation are prevalent among workers who are older, poorer, more exposed to job volatility, and from countries with higher levels of robot penetration. Perceptions over automation are positively viewed by workers with higher levels of job satisfaction, higher educational attainment, and from countries with stronger labor protection. Workers with positive perceptions of automation also tend to respond that re-education and retraining will be needed to adapt to rapidly evolving skill demands. These workers expect governments to have a role in shaping the future of work through protection of labor and new forms of social benefits. The demand for protection and benefits is more significant among women and workers that have suffered job volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet